Pertanggungjawaban Pidana bagi Pelaku Tindak Pidana Pemalsuan Hasil Visum et Repertum Ditinjau dari Kitab Undang-Undang Hukum Pidana Jo UU No. 36 Tahun 2009 Tentang Kesehatan - Annisa Nur Aurelia; Ade Mahmud (UNISBA Press, 2022)
Abstract. In an investigation, a post-mortem is very important, not only for the victim's family, but it is also important to complete the evidence of a case. Efforts to uncover a case, of course, with the help of an expert can be handled more easily, so that the authority is given by law to submit a request for an expert in matters outside the competence of the investigator. In Article 133 paragraph (1) of the Criminal Procedure Code, the expert referred to is a judicial medical expert or doctors and/or other experts who have competence or expertise in medicine. In doing or solving the problems that exist in this thesis, the author uses the study of normative juridical science. In normative juridical research, only bibliographic data or secondary data are examined, which includes primary, secondary, and tertiary legal materials. The basic theory used is the theory of responsibility and criminal acts. The regulation regarding the criminal act of falsifying the results of the post-mortem et repertum in the Health Law article does not mention sanctions or penalties for doctors who commit falsification, but in Article 189 of Law no. 36 of 2009 states that investigators or doctors are authorized to carry out visum et repertum actions. Proof of the crime of falsifying the results of the visum et repertum carried out by a doctor contained in Article 184 paragraph of the Criminal Code. The Public Prosecutor in an effort to prove the charges against the judge has submitted several pieces of evidence. The evidence that has been submitted is testimony, letters and testimony. Abstrak. Dalam lingkup penyidikan sebuah visum sangat penting keberadaannya, tidak hanya bagi keluarga korban, tetapi penting pula untuk pihak penyidik melengkapi alat bukti suatu perkara. Upaya penyidik untuk mengungkapkan suatu perkara, tentunya dalam bantuan seorang ahli dapat lebih mudah dalam penanganannya, sehingga penyidik diberikan wewenang oleh undang-undang untuk mengajukan permintaan keterangan seorang ahli dalam hal diluar dari kompetensi penyidik. Dalam Pasal 133 ayat (1) KUHAP, bahwa ahli yang dimaksud adalah ahli kedokteran kehakiman atau dokter dan/atau ahli lainnya dimana mempunyai kompentensi atau keahlian dalam kedokteran. Dalam melakukan atau pemecahan atas permasalahan yang ada dalam skripsi ini, penulis menggunakan kajian ilmu yuridis normatif. Dalam penelitian yuridis normatif yang diteliti hanya data kepustakaan atau data sekunder, yang mencakup bahan hukum primer, sekunder, dan tersier. Landasan teori yang digunakan adalah teori pertanggungjawaban dan tindak pidana. Pengaturan mengenai tindak pidana pemalsuan hasil visum et repertum dalam pasal UU Kesehatan memang tidak menyebutkan sanksi ataupun hukuman bagi dokter yang melakukan pemalsuan, tetapi dalam Pasal 189 UU No. 36 Tahun 2009 menyatakan wewenang bagi para penyidik atau dokter yang akan melakukan tindakan visum et repertum. Pembuktian tindak pidana pemalsuan hasil visum et repertum yang dilakukan oleh dokter terdapat dalam Pasal 184 ayat KUHP. Penuntut Umum dalam upaya membuktikan dakwaan kepada hakim telah mengajukan beberapa alat bukti. Alat bukti yang telah diajukan adalah keterangan saksi, surat dan keterangan terdakwa.